Using Choice-Based Assessments in an Asynchronous Online Teacher Preparation Course - Marla J Lohmann; Kathleen A Boothe (Educational Considerations, 2025)
The Universal Design for Learning (UDL) framework is becoming increasingly popular for designing instruction in the university setting. The use of the UDL framework ensures that online learning environments are inclusive and equitable for students with a variety of learning needs and preferences. This article focuses on the third UDL principle: multiple means of action and expression. One way to incorporate this UDL principle into an online classroom is to offer students choices in assignment format. This article presents a pilot research study in which students were asked their perceptions of choice-based assignments in an online graduate-level asynchronous Introduction to Special Education course. The study found five major themes in participant responses: a) reduced student stress when choices are offered, (b) enhanced learning when provided with choices, (c) knowledge can be demonstrated through student strengths, (d) selecting an assessment format can be challenging for some learners, and (e) the use of choice-based assessments encouraged respondents to use similar options in their own classrooms. Based on the results of this research, we recommend that additional research be conducted to better understand the use of choice-based assessments in teacher education.
Keywords: online learning; teacher preparation; Universal Design for Learning